Learning from Brazil's bilateral investment treaties - Paulo Cavallo (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
Investigations on the impact of BITs on FDI flows have neglected Brazil, a country that has attracted increased FDI flows despite not enacting any BIT. This Perspective, through a counterfactual analysis, argues that Brazil had not achieved its full potential and would have received additional FDI had it enacted BITs.
Keywords: 330